Scale of Resistance of Buildings to Mining Influences – Applicability Assesment Through a Case Study - NOWAK Katarzyna; STRZAŁKOWSKI Piotr; SZOJDA Leszek (Architecture, Civil Engineering, Environment)
This paper presents a case study of the impact of continuous deformations and rock mass tremors on a single-family building, typical of Upper Silesia. In the areas subjected to the influence of ground deformation, a point method for assessing the resistance of buildings to these influences has been developed by the Central Mining Institute. As part of this method, the geometric parameters, structure, materials and technical condition of the facility, as well as the ground on which the building is located, are taken into account. A case study considers a building being simultaneously subjected to continuous deformations and mining tremors. The object’s resistance is assessed according to the point method and its technical condition is assessed after revealing the influence of ground deformation. This is used to assess the validity of the point method for the building. On the basis of the analyses of the state of deformation and the impact of tremors, conclusions are drawn regarding the need to make changes to the scale used to assess the category of resistance of buildings to the effects of continuous deformation.